Innovations in Thermoelectric Technology: From Materials to Applications - Diana Enescu (Energies, 2024)
Over the past two decades, significant advances have been made in the field of energy harvesting, which involves the collection of energy from various environmental sources, including light, thermal gradients, electromagnetic radiation, and mechanical vibrations [...]